The influence of student teams achievement division and numbered heads together learning models on students' cognitive learning outcomes and critical thinking abilities - Lessil, Serly; Rumahlatu, Dominggus; Karuwal, Ritha L (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2023)
A conceptual analysis of the established functions and goals of education found that the low quality of education in Indonesia is still motivated by low student interest and learning. This problem must be addressed immediately by using learning strategies that can facilitate the development of student’s skills. Learning strategies using the STAD (Student Teams Achievement Division) and NHT (Numbered Heads Together) models are believed to be able to overcome this problem. The STAD and NHT models are cooperative learning models where both models condition students to study together in small groups and help each other. The type of research used is a quasi-experiment (Quasi experiment) which aims to determine the effect of the STAD and NHT learning models on cognitive learning outcomes and critical thinking abilities. Data were analyzed quantitatively using descriptive and inferential statistics in the form of ANCOVA analysis. The research results show that there is an influence of the STAD and NHT learning models in improving students' cognitive learning outcomes and critical thinking abilities